Potential of steel-fibre-reinforced concrete to increase RFI mitigation of antenna foundations - Li, L.; Forsyth, R.; Jackson, Carole (2013)
The preservation of a radio quiet site for both ASKAP and SKA telescopes relies on maintaining EMC compliance of all equipment. A potential source of radio frequency interference (RFI) is from leakage of RF signals from equipment housed within the antenna structure (most notably the pedestal electronics and power systems) through the foundations.